INTEGRASI MODEL PBL DENGAN PEMBELAJARAN KONTEKSTUAL PADA MATERI WUJUD ZAT DAN PERUBAHANNYA DI KELAS IV SD - Julia Adenti; KMA Fauzi; Andayani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effectiveness of the Problem Based Learning (PBL) model integrated with contextual teaching in improving students’ conceptual understanding of the states of matter and their changes in Grade IV at UPTD SDN 47 Gedong Tataan. This research employed a quasi-experimental method with a One Group Pretest–Posttest design involving 20 students. Data were collected using learning outcome tests and analyzed through the Shapiro–Wilk normality test and paired sample t-test. The results showed that the data were normally distributed (Sig. 0.658 > 0.05) and that there was a significant difference between pretest and posttest scores (Sig. 0.000 < 0.05). The mean score increased from 62.50 to 82.00, with an effect size of 2.20, categorized as very large. Therefore, the integrated PBL and contextual approach is effective in improving science learning outcomes on the topic of states of matter.